Distortion in laser micro welding of stainless steel SS304 foils - M. N., Jamaludin; Quazi, Moinuddin Mohammed; Aiman, Mohd Halil; M., Ishak (Elsevier Ltd, 2023)
Stainless Steel 304 is a fine material selection for industrial usage in laser micro welding for e-mobility applications wherein battery components are fabricated. Laser micro welding whilst very precise can produce good quality welds for thick sheets, and the risk of distortion is minimal. However, when the thickness of the sheets was reduced to a few hundred micrometres, this is where the challenge of joining emerged. Hence, this study focuses on identifying the defects that were formed by laser micro welding parameters on the geometry of the joint of Stainless Steel 304 of 100 microns thickness. Wobbling diameter and distance varied between 0.2 mm to 0.5 mm. Sample No. 5 has a higher angle distortion which was about 25° on the right side, while 11° on the left side. Whereas Sample No. 6 and No. 9 manifested no angle distortion at all. The Laser marking loop can significantly influence angle distortion on the sample that is being welded.